2015
DOI: 10.1007/s11105-015-0867-9
|View full text |Cite
|
Sign up to set email alerts
|

Western European Wild and Landraces Hazelnuts Evaluated by SSR Markers

Abstract: Hazelnut (Corylus avellana L.), a member of the family Betulaceae and the order Fagales, is native to Europe, Turkey, and the Caucasus. It has been cultivated for more than 5000 years. The majority of cultivars were selected from local wild populations over the past few centuries. Hazelnut is native to northern Portugal, with local production from landrace clonal selections. In recent years, hazelnut production has declined, and landraces are in danger of being lost. In this study, we used 16 microsatellite ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 31 publications
(33 reference statements)
2
17
1
Order By: Relevance
“…In this study, we reported for the first time the development of Single Sequence Repeats (SSR) markers in W. salutaris by employing next generation sequencing (Illumina platform). The 10 SSRs markers were validated and found to be highly polymorphic, with values similar to the ones found in other threatened species such as Acer miaotaiense (PIC = 0.604) 69 or Corylus avellana (PIC = 0.778) 70 . These markers are now available to extend W. salutaris population studies to a worldwide level.…”
Section: Discussionmentioning
confidence: 57%
“…In this study, we reported for the first time the development of Single Sequence Repeats (SSR) markers in W. salutaris by employing next generation sequencing (Illumina platform). The 10 SSRs markers were validated and found to be highly polymorphic, with values similar to the ones found in other threatened species such as Acer miaotaiense (PIC = 0.604) 69 or Corylus avellana (PIC = 0.778) 70 . These markers are now available to extend W. salutaris population studies to a worldwide level.…”
Section: Discussionmentioning
confidence: 57%
“…(1) co-dominance that makes possible the analysis of hybrids of plant commercial varieties; (2) the amplified fragments are usually small in size (100 and 300 base pairs) resulting in positive PCR amplifications even in highly degraded DNA; (3) because of the polyploid nature of the genome of several important crop species, a small number of selected SSRs are able to provide a high discrimination capacity, as reported in the section on plant biodiversity; (4) SSRs are automatable, reproducible between different laboratories (provided that some precautions are taken to uniform allele size scoring, such as sharing of standard samples between labs), easily multiplexed, and easy to score; (5) SSRs usually show a high level of polymorphism and several alleles can be detected for a single SSR locus. This latter aspect makes SSRs extremely useful also for organisms with limited or no information on the genomic sequence because a small number of markers can be enough to clearly discriminate between a large number of samples.…”
Section: Microsatellites Have a Series Of Characteristics That Make Tmentioning
confidence: 99%
“…Local varieties as breeds, landraces, ecotypes, and ancient varieties, which have been rarely subjected to breeding, are usually characterized by high genetic variability and genotypes. These germplasm resources are well adapted to both local needs and environmental conditions with good fitness for the anthropic and natural environments in which they have evolved [2,3].…”
Section: Microsatellites Have a Series Of Characteristics That Make Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In Portugal, hazelnut production orchards are mainly located in north, due to its favourable edaphoclimatic conditions. 1 Nonetheless, the irregular pattern of climate conditions in recent years has contributed to irregular yields with reflex in chemical and physical properties, and, thus, in the nut nutritional quality. Hazelnut, due to its pleasant sensory characteristics, constitutes one of the most important raw materials for the pastry and chocolate industry, 2 being highly considered since it adds flavour and texture to bakery, confectionery, cereal, dairy, salad, entrée, sauce and dessert formulations.…”
Section: Introductionmentioning
confidence: 99%